Use of the caffeine-halothane contracture test for the diagnosis of malignant hyperthermia in Brazil - Sudo,R.T. (2010)
Malignant hyperthermia (MH) is a pharmacogenetic disease triggered by volatile anesthetics and succinylcholine. Deaths due to MH have been reported in Brazil. The first Malignant Hyperthermia Diagnostic and Research Center in Latin America was inaugurated in 1993 at the Federal University of Rio de Janeiro, Brazil. The center followed the diagnostic protocols of the North America MH Group, in which the contractures of biopsies from the vastus lateralis muscle are analyzed after exposure to caffeine and halothane (CHCT). CHCT was performed in individuals who survived, their relatives and those with signs/symptoms somewhat related to MH susceptibility (MHS). Here, we report data from 194 patients collected over 16 years. The Southeast (N = 110) and South (N = 71) represented the majority of patients. Median age was 25 (4-70) years, with similar numbers of males (104) and females (90). MHS was found in 90 patients and 104 patients were normal. Abnormal responses to both caffeine and halothane were observed in 59 patients and to caffeine or halothane in 20 and 11 patients, respectively. The contracture of biopsies from MHS exposed to caffeine and halothane was 1.027 ± 0.075 g (N = 285) and 4.021 ± 0.255 g (N = 226), respectively. MHS was found in patients with either low or high blood creatine kinase and also, with a low score on the clinical grading scale. Thus, these parameters cannot be used with certainty to predict MHS. We conclude that the CHCT protocol described by the North America MH Group contributed to identification of MHS in suspected individuals at an MH center in Brazil with 100% sensitivity and 65.7% specificity.